Dynamics of Education Cost Policy in Higher Education - Sahrun Nisyak, Fani Nikmatul; Suryadi, Suryadi; Wike, Wike (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the dynamics of the tuition fee policy at Universitas Brawijaya, particularly in the Faculty of Agriculture and the Faculty of Administrative Sciences, by examining student perceptions and the social impacts of tuition fee changes. Using a descriptive qualitative approach and a case study design, the research was conducted at these two faculties, representing different academic cluster STEM and SSH. Informants were selected through purposive sampling, consisting of eight active students who experienced significant tuition increases. Data were collected through in-depth interviews and documentation of official university regulations, tuition data, and campus news reports. Data analysis employed the interactive model of Miles and Huberman, and Fischer’s policy dynamics theory was used to interpret findings across five indicators: power and politics, knowledge and information, actor interaction, change and adaptation, and conflict of values and interests. Results show that tuition fees increased significantly after 2019, triggering greater economic disparity and dissatisfaction among students. Although faculties attempted to respond with measures like Crisis Centers and fee reductions, the study concludes that policy reform is needed particularly in communication, transparency, and student involvement to support a more equitable education financing system.